BROAD Group : Chinese innovation in the air - Williamson, Peter J. ([London] : SAGE, 2016)
This case explores how the Chinese company, BROAD Group, innovated by taking an existing technology (non-electric air conditioning) and re-engineering it to dramatically improve the energy efficiency and reduce the environmental impact of large-scale air conditioning systems used in applications as diverse as skyscrapers and airports.
Originally Published in: Williamson, P. (2011). BROAD Group: Chinese innovation in the air. Cambridge: University of Cambridge, Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Technological innovations -- Economic aspects -- Case studies